Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual-Beli Melalui E-Commerce - Alfitriani, Alfitriani; Octavianty, Octavianty; Mutmainna, Mutmainna; Pransisto, Johamran (Jurnal Litigasi Amsir, 2022)
Behind the rapid advances in technology, especially the development of the Internet in Indonesia, there are a lot of negative things being targeted and harassed people who like the Internet that we usually hear as Internet surfers. For business and trade in the internet media is required understanding, seriousness, and the will of its own. In an agreement is often one of the parties/stakeholders have to face difficult conditions and ultimately contact/agreement that has been agreed can not walk/run well/as appropriate. Factors that make it difficult events that can occur due to deliberate or accidental. Default is a condition/situation that can be done by one of the parties or the parties to an engagement which can be generally described that the treaty was not executed properly and not in accordance with what has been agreed from the beginning. Plunge into the business of buying and selling online/transact electronically (e-commerce) is a rare move but it’s a lifestyle and trend in this medern era, but must also watch out and be noticed. Among the things that can later be referred to as a form of default. Default in the purchase agreement online can take many forms and sometimes we experienced it and still not sensitized that this/these events can be called an act of default. For example: late payment, no payment, send the goods but not in accordance with what was agreed, but too late to send goods, which in turn raises certain legal consequences.